PENGARUH KOMUNIKASI ORGANISASI, KEMAMPUAN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI NON MEDIS DI RSUD Dr. HARJONO S PONOROGO - Budiono, Budiono; Tri Haryanto, Aris; Suryo Sardjono, Herning (Master of Public Administration, Universitas Slamet Riyadi, 2024)
Purpose of this studies to know the effect of organizational communication, work ability and leadership on the performance of non-medical employees. This type of research is explanatory research conducted at RSUD Dr. Harjono S Ponorogo. The research population was non-medical employees at Dr. RSUD. Harjono S Ponorogo, totaling 119 people and all of them were used as samples use population research techniques. Data collection techniques use questionnaires and literature study. The data analysis technique use multiple linear regression. The research results show that organizational communication has an effect on the performance of non-medical employees with a calculated t value of 4.010 with a p value (0.000) < 0.05. Work ability effect on performance of non-medical employees with a calculated t value of 4.365 with a p value (0.000) < 0.05. Leadership effect on performance of non-medical employees with a calculated t value of 4.095 with a p value (0.000) < 0.05. Organizational communication, work ability and leadership effect the performance of non-medical employees simultaniously with a p value of 0.000 <0.05.